Post‐operative outcomes in the elderly following colorectal cancer surgery. Issue 3 (22nd October 2020) - Park, Hyerin; Parys, Simon; Tan, Jonathan; Entriken, Fiona; Hodder, Rupert
Abstract: Background: Despite the prevalence of colorectal cancer in the elderly, there has been a lack of recent studies examining surgical outcomes in these patients. Post‐operative outcomes of colorectal cancer surgeries in those aged 80 and above will be compared to those younger than 80. Methods: A retrospective study was conducted of adults receiving surgical resections at a single tertiary centre for colorectal cancer diagnosed between January 2017 and December 2019. Patient demographics, mode of presentation, tumour demographics, operative data and post‐operative outcomes were investigated. Results: Of the 326 patients included, 56 were aged 80 and above. Older patients were more likely to be female ( P = 0.02), present with surgical emergencies or from other workup rather than through screening ( P = 0.002), have more locally advanced cancers ( P = 0.009) and receive less neoadjuvant therapy ( P = 0.016). Despite this, they had comparable outcomes to those younger than 80 in terms of length of stay ( P = 0.21) and rates of complications including mortality ( P = 0.67). Conclusion: With appropriate patient selection and management, elderly patients can achieve comparable post‐operative outcomes to their younger counterparts. Abstract : Traditionally, older people have been viewed as high‐risk surgical candidates. In our cohort, we found that patients aged 80 years and above were more likely to present with surgical emergencies or from other workup and have more locally advanced cancers than those younger than 80. Despite this, the two groups had comparable outcomes in terms of length of stay and rates of complications.